2010
DOI: 10.1007/s10162-010-0207-6
|View full text |Cite
|
Sign up to set email alerts
|

Complex Stapes Motions in Human Ears

Abstract: It has been reported that the physiological motion of the stapes in human and several animals in response to acoustic stimulation is mainly piston-like at low frequencies. At higher frequencies, the pattern includes rocking motions around the long and short axes of the footplate in human and animal ears. Measurements of such extended stapes motions are highly sensitive to the exact angulation of the stapes in relation to the measurement devices and to measurement errors. In this study, velocity in a specific d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 14 publications
6
67
0
1
Order By: Relevance
“…Using a video measuring system, Gyo et al (1987) observed predominant piston-like movements only at low frequencies and complex movements at higher frequencies. Other studies in human and animals are in accordance with these findings (Asai et al 1999;Decraemer & Khanna 1999;Voss et al 2000;Hato et al 2003;Stenfelt and Goode 2005;Decraemer et al 2007;Ravicz et al 2008;Sim et al 2010a). Some previous studies, assuming that the annular ring of the stapes restricts motions of the stapes footplate in the plane of the footplate, considered piston-like motions (i.e., the translational motion in a direction perpendicular to the stapes footplate) and two rocking-like motions of the stapes (i.e., the two rotational motions along the long and short axes of the footplate) as primary motion components of the mammal stapes.…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Using a video measuring system, Gyo et al (1987) observed predominant piston-like movements only at low frequencies and complex movements at higher frequencies. Other studies in human and animals are in accordance with these findings (Asai et al 1999;Decraemer & Khanna 1999;Voss et al 2000;Hato et al 2003;Stenfelt and Goode 2005;Decraemer et al 2007;Ravicz et al 2008;Sim et al 2010a). Some previous studies, assuming that the annular ring of the stapes restricts motions of the stapes footplate in the plane of the footplate, considered piston-like motions (i.e., the translational motion in a direction perpendicular to the stapes footplate) and two rocking-like motions of the stapes (i.e., the two rotational motions along the long and short axes of the footplate) as primary motion components of the mammal stapes.…”
Section: Introductionsupporting
confidence: 71%
“…The two rocking-like components around the long and short axes of the footplate were summarized as only one rocking component, but they could have different influences. Compared to the motion forms found in guinea pigs, human stapes motions show somewhat higher rocking components, especially in the higher frequency range (Hato et al 2003;Sim et al 2010a). Therefore, a larger contribution of the rocking-component is expected in human hearing.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…approximately 7 dB instead of 4 dB at low frequencies), the mean responses for the 3 incus conditions show even greater similarity than for the stapes responses, particularly with regard to the amplitude responses, where there is near superposition up to stimulus frequencies as high as 6 kHz. The larger mean differences between the stapes responses for the 3 incus conditions, compared with those for the RW, is possibly due to the fact that the stapes footplate is known to have significant non-piston-like motion at high frequencies [Guinan and Peake, 1967;Decraemer et al, 2007;Sim et al, 2010], but nevertheless the middle-ear pressure gain as a function of frequency is known to be relatively smooth [Decraemer et al, 2007]. In this sense, the RW responses -being perhaps a more direct measure of intracochlear fluid dynamics -provide even greater confidence in the conclusion that the presence of the FMT has an insignificant effect on cochlear input.…”
Section: Acoustic Stimulationmentioning
confidence: 99%
“…Sound measurements along this pathway help to determine sound transmission in normal hearing and conductive hearing disorders. The findings from these experimental approaches and the deduced theoretical models contribute to the understanding of hearing and have led to improved hearing rehabilitation with surgical interventions and implantable hearing devices [1]- [4]. Further investigations of the biomechanical hearing process are important for optimization of future hearing rehabilitation methods.…”
Section: Introductionmentioning
confidence: 99%